Cardiovascular Complications in Patients with Turner’s Syndrome - Kostopoulou, Eirini; Bosdou, Julia K.; Anagnostis, Panagiotis; Stevenson, John C.; Goulis, Dimitrios G. (Current Pharmaceutical Design, 2020)
Turner's or Turner syndrome (TS) is the most prevalent chromosomal abnormality in live female births. Patients with TS are predisposed to an increased risk of cardiovascular diseases (CVD), mainly due to the frequently observed congenital structural cardiovascular defects, such as valvular and aortic abnormalities (coarctation, dilatation, and dissection). The increased prevalence of cardiometabolic risk factors, such as arterial hypertension, insulin resistance, diabetes mellitus, dyslipidaemia, central obesity, and increased carotid intima-media thickness, also contribute to increased morbidity and mortality in TS patients. Menopausal hormone therapy (MHT) is the treatment of choice, combined with growth hormone (GH). Although MHT may, in general, ameliorate CVD risk factors, its effect on CVD mortality in TS has not yet been established. The exact effect of GH on these parameters has not been clarified. Specific considerations should be provided in TS cases during pregnancy, due to the higher risk of CVD complications, such as aortic dissection. Optimal cardiovascular monitoring, including physical examination, electrocardiogram, CVD risk factor assessment, and transthoracic echocardiography, is recommended. Moreover, the cardiac magnetic resonance from the age of 12 years is recommended due to the high risk of aortic aneurysm and other anatomical vascular complications.
Keywords: aortic dilatation; aortic dissection